2009
DOI: 10.1021/jp904784b
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dynamics and Two-Photon Absorption Cross Sections of Fluorescent Diphenyl-TinIV Derivatives with Schiff Bases: A Comparative Study of the Effect of Chelation from the Ultrafast to the Steady-State Time Scale

Abstract: Schiff bases bearing an intramolecular hydrogen bond are known to undergo excited-state intramolecular proton transfer and E-Z isomerization, which are related to their thermochromism and solvatochromism properties. In this study, we explored these ultrafast photoinduced processes for two doubly hydroxylated Schiff bases, salicylidene-2-aminophenol and 2-hydroxynaphthylmethylidene-2-aminophenol. From comparisons with our previously reported results for the parent monohidroxylated Schiff base salicylideneanilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Although the maximum was found at around 750 nm in the three solvents, in chloroform the TPA response is enhanced ( Figure 58) and it is possible to observe a second absorption at 1000 nm that is roughly observed in DMSO and THF. This is explained because the two-photon excitation fluorescence comes from the lowest excited state S1 [48] as reported by Peon for this type of complex [109]. In this case, the excited state is accessible through excitation at the bands located around 400 nm and 500 nm in the OPA spectra explaining the presence of the second band.…”
Section: Third-order Nlo Propertiessupporting
confidence: 55%
See 2 more Smart Citations
“…Although the maximum was found at around 750 nm in the three solvents, in chloroform the TPA response is enhanced ( Figure 58) and it is possible to observe a second absorption at 1000 nm that is roughly observed in DMSO and THF. This is explained because the two-photon excitation fluorescence comes from the lowest excited state S1 [48] as reported by Peon for this type of complex [109]. In this case, the excited state is accessible through excitation at the bands located around 400 nm and 500 nm in the OPA spectra explaining the presence of the second band.…”
Section: Third-order Nlo Propertiessupporting
confidence: 55%
“…Diorganotin Schiff bases are another type of tin derivatives capable of third order NLO properties. Peon et al [109] described a series of diphenyl tin(IV) Schiff bases (Figure 54), the fluorescence in these complexes are up to 50 times larger than the free base due to the rigidity imposed by the tin center. Li et al [108] reported the study of tetrachloro (1,10-phenanthroline-N,N') tin(IV) listed in Table 9 and their NLO properties.…”
Section: Third-order Nlo Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results corroborate the somewhat similar findings by Peón et al for photochemical properties of coumarins, Schiff bases, etc. (Esquivelzeta-Rabell, Peon, & Cuevas, 2009;Morales-Cueto, Esquivelzeta-Rabell, Saucedo-Zugazagoitia, & Peon, 2007;Rodriguez-Córdoba, Zugazagoitia, Collado-Fregoso, & Peon, 2007;Zugazagoitia et al, 2010).…”
Section: Hydroxyl Radical Reactionsmentioning
confidence: 99%
“…On the other hand, Schiff bases with an intramolecular hydrogen bond have been extensively used as model systems to study fundamental photophysical processes, such as excited‐state intramolecular proton transfer (ESIPT), photochromism, solvatochromism, and thermochromism . This kind of derivatives could also act as versatile chelating ligands to complex with metal ions . Recently, some fluorescent sensors based on diarylethenes with a Schiff base unit have been reported .…”
Section: Introductionmentioning
confidence: 99%